The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1111/jpn.13754
|View full text |Cite
|
Sign up to set email alerts
|

Does the metabolizable energy influence the performance, carcass characteristics and biochemical parameters of European quails from 28 to 42 days of age?

Abstract: This study was conducted to determine the metabolizable energy (ME) requirement for quails (Cortunix cortunix cortunix) from 28 to 42 days of age. Four hundred and twenty quails were distributed in a completely randomized design, with 5 treatments (2950, 3000, 3050, 3100 and 3150 kcal of ME/kg of feed), 7 replicates and 12 birds per experimental unit. Performance, relative weights of organs and viscera, carcass characteristics, meat quality, body composition and blood parameters of the birds were evaluated. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
(46 reference statements)
0
0
0
Order By: Relevance
“…Feed intake, influenced quadratically by the main and interaction effects of ME and DL in the grower phase, tended to decrease with increasing ME levels, thereby improving feed conversion ratio. Classen (2017) and Jesus et al (2023) observed that, by increasing ME levels in grower diets for Japanese quail, there was a significant decrease in feed intake and an improvement in feed conversion ratio throughout the experimental period. These findings suggest that, during growth, feed energy content is a crucial parameter.…”
Section: Animal Performancementioning
confidence: 97%
“…Feed intake, influenced quadratically by the main and interaction effects of ME and DL in the grower phase, tended to decrease with increasing ME levels, thereby improving feed conversion ratio. Classen (2017) and Jesus et al (2023) observed that, by increasing ME levels in grower diets for Japanese quail, there was a significant decrease in feed intake and an improvement in feed conversion ratio throughout the experimental period. These findings suggest that, during growth, feed energy content is a crucial parameter.…”
Section: Animal Performancementioning
confidence: 97%